Hypoxic Ischemic Encephalopathy Indicators of Sarnat and Sarnat Scoring in Neonatal Subjects with Perinatal Asphyxia. - SADEGHI MOGHADDAM, Parvaneh; AGHAALI, Mohammad; MODARRESY, Seyede Zeinab; SHAHHAMZEI, Samira; ALJABOORI, Maryam (Iranian Journal of Child Neurology)
Objectives Hypoxic-ischemic encephalopathy (HIE) is still a relevant cause of neonatal mortality and morbidity. HIE severity can predict long-term outcomes. Sarnat staging is one of the most common methods used to evaluate HIE severity. However, an ongoing urge exists to find other accurate and affordable ways to accompany this clinical staging for HIE. This study aimed to evaluate the relationship between cerebral arteries' resistive indices and other hypoxic-ischemic encephalopathy indicators using Sarnat scoring of newborns subjected to perinatal asphyxia. Materials & Methods In this retrospective study, 76 neonates with gestational age ≥34 weeks affected with HIE were investigated. The patients were categorized into three groups according to Sarnat staging: I, II, and III. Initially, perinatal data were analyzed to assess the correlation between HIE severity and various factors such as gestational age, type of delivery, Apgar scores, necessity for resuscitation, and requirement for respiratory assistance. Notably, these relationships were significant. Results Examining various symptoms in different HIE stages showed that the incidence of coagulopathy was significantly higher in severe HIE neonates than in mild neonates. Eventually, proposedly, cranial arterial Doppler indices, i.e., the anterior cerebral artery's resistive index (RI), significantly differed between HIE stage groups. Conclusion This study represented a combination of available and affordable data to achieve early HIE staging, including perinatal data, clinical symptoms, and a bedside Doppler ultrasonography of cerebral perfusion. Higher cranial artery RI was associated with severe HIE and could be considered for therapeutic hypothermia, which may reduce HIE mortality and morbidity.